Comparison of upright balance in stroke, Parkinson and multiple sclerosis. (3rd August 2015) - Cattaneo, D.; Carpinella, I.; Aprile, I.; Prosperini, L.; Montesano, A.; Jonsdottir, J.
Abstract : Objective: Multiple sclerosis (MS), Parkinson's disease (PD) and stroke (ST) subjects show balance impairments due to damage of the balance control system. The objective of the study was to assess the impact of MS, PD and ST on upright posture in eyes open condition and when visual and/or proprioceptive inputs are altered. Materials and methods: A total of 188 subjects with MS ( n = 80), PD ( n = 58) and ST ( n = 50), mean age (SD), 57.9 (14.6) years, and 32 healthy subjects (HS) aged 53.7 (15.7) years were assessed by a stabilometric platform in a cross‐sectional study. Results: Compared to HS, MS showed large deviations from normal performances with respect to magnitude ( P < 0.001) and regularity ( P < 0.05) of body sway irrespective of the altered sensory information. Similarly to MS, PD showed large and abnormal levels of body sway ( P < 0.001) and postural tremor ( P < 0.05), while ST was the least impaired except for an asymmetrical distribution of body weight between legs ( P < 0.001). Finally, the MS group compared to PD and ST showed the largest body instability after eye closure ( P < 0.05) and when visual and proprioceptive inputs were removed ( P < 0.05). PD showed instability mainly after the alteration of proprioceptive inputs ( P < 0.05), while ST showed the smallest increase of body instability when sensory inputs were reduced. Discussion: Objective assessment revealed pathology‐specific balance disorders and showed the differential impact of MS, PD and ST on the ability to use sensory information for balance control.